PENGARUH PEMBERIAN VARIASI DOSIS DAUN UBI JALAR (Ipomoea batatas) TERHADAP KOLESTEROL DARAH PADA AYAM KAMPUNG - Reni Rakhmawati (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
Improving the quality of free-range chicken meat is not only in improving feeding and maintenance management, it is necessary to increase the genetic quality and maintain its physiological characteristics that reflect the condition of poultry (chicken) including blood cholesterol in free-range chickens. This study aims to determine the effect of varying doses of sweet potato leaves (Ipomoea batatas) on blood cholesterol content in native chickens. The design used was RAL. The research material consisted of 4 treatments with 3 repetitions. The chickens used are native chickens, with maintenance until the age of 12 weeks. The treatments in this study consisted of P0 (chicken feed/control), P1 (chicken feed + 5% sweet potato leaves), P2 (chicken feed + 10% sweet potato leaves), and P3 (chicken feed + 15% sweet potato leaves). The analysis includes the homogeneity of the research sample. The final analysis with ANOVA with a significance level of 5%, if there is an effect continued with Duncan's test. The results of this study showed no significant effect (P > 0.05) on the blood cholesterol of native chickens. The blood cholesterol content in the administration of variations in doses of sweet potato leaves (Ipomoea batatas) did not significantly affect the results of the highest blood cholesterol content in the P2 treatment (279 mg/dl) and the lowest result in the P0 treatment (225.67 mg/dl).